Changes in gene expression in human skeletal stem cells transduced with constitutively active Gsα correlates with hallmark histopathological changes seen in fibrous dysplastic bone - Raimondo, Domenico (2021)
Fibrous dysplasia (FD) of bone is a complex disease of the skeleton caused by dominant activating mutations of the GNAS locus encoding for the α subunit of the G protein-coupled receptor complex (Gsα). The mutation involves a substitution of arginine at position 201 by histidine or cysteine (GsαR201H or R201C), which leads to overproduction of cAMP. Several signaling pathways are implicated downstream of excess cAMP in the manifestation of disease. However, the pathogenesis of FD remains largely unknown. The overall FD phenotype can be attributed to alterations of skeletal stem/progenitor cells which normally develop into osteogenic or adipogenic cells (in cis), and are also known to provide support to angiogenesis, hematopoiesis, and osteoclastogenesis (in trans). In order to dissect the molecular pathways rooted in skeletal stem/progenitor cells by FD mutations, we engineered human skeletal stem/progenitor cells with the GsαR201C mutation and performed transcriptomic analysis. Our data suggest that this FD mutation profoundly alters the properties of skeletal stem/progenitor cells by pushing them towards formation of disorganized bone with a concomitant alteration of adipogenic differentiation. In addition, the mutation creates an altered in trans environment that induces neovascularization, cytokine/chemokine changes and osteoclastogenesis. In silico comparison of our data with the signature of FD craniofacial samples highlighted common traits, such as the upregulation of ADAM (A Disintegrin and Metalloprotease) proteins and other matrix-related factors, and of PDE7B (Phosphodiesterase 7B), which can be considered as a buffering process, activated to compensate for excess cAMP. We also observed high levels of CEBPs (CCAAT-Enhancer Binding Proteins) in both data sets, factors related to browning of white fat. This is the first analysis of the reaction of human skeletal stem/progenitor cells to the introduction of the FD mutation and we believe it provides a useful background for further studies on the molecular basis of the disease and for the identification of novel potential therapeutic targets.